IP Web-Based Scada System - Muhamad Azam Bin Ahmad (2023)
This paper is about designing a low-cost SCADA system that can remotely control and monitor the process in the industry[1]. Programmable Logic Circuit (PLC) is a common controller used as field devices because they are more versatile and can manage complex automation systems. But the cost to design the PLC is expensive for a small industry that intends to use SCADA technology. This project is suitable for the small industry to control simple processes such as to monitor the water level or temperature and to turn On or Off the equipment such as pump and motor. This project will be using Raspberry Pi and a controller and Cayenne Internet of Thing (IoT) platform as a Graphical User Interface (GUI). All the systems can be access and control remotely via the internet by using smartphones and computers. This project consists of two parts, build the hardware to shows the digital output and combine python programming software with the Cayenne IoT platform to perform control and analog data monitoring. The output of this project can be control through a virtual button of the phones or computer and also using a manual push button on the SCADA system. The relay will be connected to the General Purpose Input Output (GPIO) of the Raspberry Pi to turn On/Off the equipment. Analog and digital input also can be monitor by connecting the sensors to the GPIO pins. The value of analog and digital input can be display in graphical form to access the situation of the systems. This will help the operator to monitor and make decisions on their process plant.